Pengembangan Media Gambar dengan Pendekatan Kontekstual pada Pembelajaran Tematik Sekolah Dasar - Janah, Pathul; Subhani, Armin; Haritani, Hartini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to describe how to develop image media with a contextual approach, determine the validity of image media with a contextual approach, find out the practicality of image media with a contextual approach, and determine the effectiveness of image media with a contextual approach in elementary school thematic learning. This research and development uses a 4D development model that has been simplified into 3D with the stages of define, design, and develop. The type of data used in this study uses primary data. The instruments used in this study were: observation, interviews, and questionnaires. The results of the media design validation test and the content of the image media design material were considered valid with values of 97.14%, 92.72% and 83.63%. Student responses to individual and group tests were considered very positive, as seen from the lowest student response scores of 78% and the highest 90%. The conclusion of this study is that based on the results of trials and analysis, it is known that picture media with a contextual approach to thematic learning is very effective, as seen from the achievement of students and teachers who have reached the minimum standard. Keywords: Contextual Approach, Image Media, Thematic.